Poverty Analysis In Riau Province : Spatial Econometric Approach - Farhan, Muhammad; Fikry Hadi, Muhammad; Hidayat, Muhammad (Publikasi Indonesia, 2024)
Poverty is indeed a major problem in a country, many various poverty factors occur. This study was conducted to see the influence of the relationship between poverty areas and other poverty areas, with an econometric spatial approach. It is hoped that the approach model can analyze the factors that affect the category of poor people in Riau Province. Data analysis using Spatial Regression with the help of Geoda software to perform spatial tests. with the data used is the Number of Poor People as the dependent variable, while the independent variables are GDP ADHK, District Minimum Wage, Human Development Index. The results of this study show that spatially poverty, minimum wage, HDI, and GRDP have a positive spatial relationship. Meanwhile, according to LISA (Local Indicator of Spatial Autocorrelation) as a whole, significant clusters in each variable vary in each region. However, the relationship between GRDP, HDI, and MSEs is not significant for poverty.